2009
DOI: 10.1093/bioinformatics/btp019
|View full text |Cite
|
Sign up to set email alerts
|

Sparse linear discriminant analysis for simultaneous testing for the significance of a gene set/pathway and gene selection

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 27 publications
0
99
0
Order By: Relevance
“…It is also interesting to note that, in the case D = W , SCF requires about only three iterations to achieve a highly accurate solution (with residual ϱ up to 10 −9 ) for a random problem (1.1). In addition, we also observed that, except for the case n = 100, all these algorithms approach the same objective value for each test problem; in several test 4 In the MATLAB environment, the generic Riemannian trust-region package for the optimization of functions defined on Riemannian manifolds is available at http://www.math.fsu.edu/~cbaker/GenRTR/ 5 The MATLAB code sg_min of the latest version (version 2.4.3) is available at http://web.mit.edu/~ripper/www/sgmin.html 6 Because sg_minminimizes a function on the Stiefel manifold, we use −f (x) instead of f (x). 7 We point out that it does not lose any generality to assume that B is also positive definite as we can shift B to B + ξ W so that it is positive definite but with the maximizers unchanged.…”
Section: Preliminary Numerical Experimentsmentioning
confidence: 60%
See 1 more Smart Citation
“…It is also interesting to note that, in the case D = W , SCF requires about only three iterations to achieve a highly accurate solution (with residual ϱ up to 10 −9 ) for a random problem (1.1). In addition, we also observed that, except for the case n = 100, all these algorithms approach the same objective value for each test problem; in several test 4 In the MATLAB environment, the generic Riemannian trust-region package for the optimization of functions defined on Riemannian manifolds is available at http://www.math.fsu.edu/~cbaker/GenRTR/ 5 The MATLAB code sg_min of the latest version (version 2.4.3) is available at http://web.mit.edu/~ripper/www/sgmin.html 6 Because sg_minminimizes a function on the Stiefel manifold, we use −f (x) instead of f (x). 7 We point out that it does not lose any generality to assume that B is also positive definite as we can shift B to B + ξ W so that it is positive definite but with the maximizers unchanged.…”
Section: Preliminary Numerical Experimentsmentioning
confidence: 60%
“…In theory, one can assume, without loss of generality, that D is also positive definite and even diagonal because of the unit sphere constraint. Problem (1.1) can arise from some real-world applications, for example, in the downlink of a multi-user MIMO system [1] and in the sparse Fisher discriminant analysis in pattern recognition [2][3][4][5]. Moreover, it has been pointed out [5] that there are several other problems that can be equivalently transformed to (1.1).…”
Section: Introductionmentioning
confidence: 99%
“…not all genes in a gene set are regulated at the expression level in a given physiological condition. Some methods were developed to select subsets of genes simultaneously with the generation of gene set statistics [45][46] , utilize covariance structure in testing 47 , or incorporate regulatory network connectivity 48 . Some of the gene set analysis methods have been previously reviewed and compared [38][39][40][49][50][51][52] .…”
Section: Pathway/metabolite Set Testingmentioning
confidence: 99%
“…In recent years, many high-dimensional generalizations of linear discriminant analysis have been proposed (Tibshirani et al, 2002;Trendafilov and Jolliffe, 2007;Clemmensen et al, 2011;Donoho and Jin, 2008;Fan and Fan, 2008;Wu et al, 2008;Shao et al, 2011;Cai and Liu, 2011;Witten and Tibshirani, 2011;Mai et al, 2012;Fan et al, 2012). In the binary case, the discriminant direction is β = Σ −1 (µ 2 − µ 1 ).…”
Section: Introductionmentioning
confidence: 99%